Contributions from the Neurosciences for the Understanding of Learning Processes in Educational Contexts - Araya-Pizarro, Sebastián C. (2020)
In the current scientific literature refers to the contributions from the Neurosciences for the understanding of learning processes. This is how, as well as from the branches of Neurosciences, such as Cognitive Neuroscience, specific contributions are bornthat facilitates the understanding of these processes. On the other hand, Neuroeducation as a new discipline proposes to take these contributions from the Neurosciences for the improvement of educational practices, and thereby optimize learning. The objective of this article is to analyze the theoretical contributions in force from the Neurosciences, to understand the learning situated in educational contexts. For this, the relationship of the concepts Neuroscience, Cognitive Neuroscience and Neuroeducation is alluded to. In addition, the main contributions from the Neurosciences are analyzed to understand the processes of neuroplasticity, and the impact of emotions, sleep quality, physical activity and social contexts in learning. Finally, we discuss the importance of these contributions and how they guide the teaching role and educational practices so that they allow for meaningful learning.